Integration of Infrastructure Asset Management in Disaster Mitigation and Sustainable Development Strategies in Densely Populated Coastal Areas: A Literature Review - Poetra, Auliya Wildana; Kurniadi, Anwar; Ali, Yusuf; Setiawibawa, Rachmat (International Journal of Education, Vocational and Social Science, 2026)
Densely populated coastal areas face serious threats due to sea level rise and land subsidence, which accelerate the deterioration of mitigation infrastructure. This study aims to formulate the integration of Infrastructure Asset Management (IAM) into sustainable disaster mitigation strategies using the Systematic Literature Review (SLR) method with the PRISMA protocol. From 345 initial documents, 20 leading articles were selected for in-depth analysis. The results of the study show that coastal resilience requires a transformation from reactive maintenance to proactive risk-based management. Key findings identify three pillars of integration: (1) the use of digital technologies (BIM, GIS, Digital Twin) for real-time monitoring; (2) innovation in corrosion-resistant materials and hybrid (green-gray) infrastructure approaches; and (3) the application of Life Cycle Cost Analysis (LCCA) for long-term budget efficiency. The study concludes that synchronizing data governance across agencies is crucial to the success of mitigation efforts. The practical implication emphasizes that adopting an adaptive IAM framework can minimize the risk of structural failure and ensure public safety amid global climate uncertainty.